Effect of HTST Thermal Treatments on End-Use Quality Characteristics of Goat Milk - B. D. Rohitha Prasantha; K. M. S. Wimalasiri (International Journal of Food Science)
Goat milk samples were pasteurized at high-temperature (72°C, 75°C, and 81°C) and in short-time (15 s and 25 s) combinations. Physical, chemical and microbial qualities of the pasteurized milk samples were evaluated 0, 2, 3, and 4 weeks of storage at 4°C. Despite the different thermal treatments, specific-gravity and viscosity were comparatively stable immediately after pasteurization (IAP). The viscosity of pasteurized milk at 81°C showed significant increase (P<0.05) from 1.58 ± 0.18 to 2.30 ± 0.15 mPa s during four weeks of storage. Relative lightness “L” value decreased by about 10% during the storage period of 81°C pasteurization samples. Acidity increased with heat treatment irrespective of holding time, but in 81°C pasteurized sample higher acidity was developed at end of the storage. Fat oxidation 2-3 times higher at 81°C than 72°C pasteurized samples. Total protein (TP%) and nonprotein nitrogen contents were stable IAP but TP reduced significantly (P<0.05) at two weeks storage. The whey protein denaturation increased with pasteurization treatments and storage time. Antioxidant activity of raw goat milk was 34.8 ± 5.01 μmol l−1 and was decreased by 20–43% IAP compared to raw milk samples, but gradually increased during storage. IAP, mesophilic counts were in the range of 980–110 cfu ml−1 (72°C/15–81°C/25 s) and increased from 2236 to 680 cfu ml−1 samples stored at 4 weeks. Results showed that best quality stability of pasteurized goat milk achieved by heat treatments between 72°C/25 s and 75°C/25 s heat treatments up to 3 weeks of storage under 4°C.